Five years of Awami rule - Miah, M. Maniruzzaman (Dhaka : Gatidhara, 2001)
Covers the period, 1996-2001; articles previously published in Dhaka courier, weekly.
Keywords: Awami League; Bangladesh -- Politics and government -- 1971-